A multiparadigm language for developing agent-oriented applications - Kam Wing Ng; Linpeng Huang; Yongqiang Sun (Technology of Object Oriented Languages and Systems. 27th, 1998)
I/sup +/ is a multiparadigm language for object oriented declarative programming as well as parallel programming. If is an integration of three major programming paradigms: object oriented, logic and functional with salient features for modelling distributed applications, however, I/sup +/ has a number of limitations in developing multi agent applications as well as programming mobile agents. We introduce a dedicated set of primitives necessary for communication among agents and an HTTP based infrastructure to serve mobile agents to I/sup +/. The resultant language is called I* and we argue that I* is a language suitable for the development of agent oriented applications.